Histological development of the digestive system of the Amazonian pimelodid catfish Pseudoplatystoma punctifer. (21st July 2014) - Gisbert, E.; Moreira, C.; Castro-Ruiz, D.; Öztürk, S.; Fernández, C.; Gilles, S.; Nuñez, J.; Duponchelle, F.; Tello, S.; Renno, J. F.; García-Dávila, C.; Darias, M. J.
<x content-type="archive" xml:space="preserve">Abstract</x> The organogenesis of the digestive system was described in the Amazonian pimelodid catfish species Pseudoplatystoma punctifer from hatching (3.5 mm total length, TL) to 41 days post-fertilization (dpf) (58.1 mm TL) reared at 28°C. Newly hatched larvae showed a simple digestive tract, which appeared as a straight undifferentiated and unfolded tube lined by a single layer of columnar epithelial cells (future enterocytes). During the endogenous feeding period, comprised between 20 and 96 h post-fertilization (3.5 to 6.1 mm TL), the larval digestive system experienced a fast transformation with the almost complete development and differentiation of most of digestive organs (buccopahrynx, oesophagus, intestine, liver and exocrine pancreas). Yolk reserves were not completely depleted at the onset of exogenous feeding (4 dpf, 6.1 mm TL), and a period of mixed nutrition was observed up to 6 to 7 dpf (6.8 to 7.3 mm TL) when yolk was definitively exhausted. The stomach was the organ that latest achieved its complete differentiation, characterized by the development of abundant gastric glands in the fundic stomach between 10 and 15 dpf (10.9 to 15.8 mm TL) and the formation of the pyloric sphincter at the junction of the pyloric stomach and the anterior intestine at 15 dpf (15.8 mm TL). The above-mentioned morphological and histological features observed suggested the achievement of a digestive system characteristic of P. punctifer juveniles and adults. The ontogeny of the digestive system in P. punctifer followed the same general pattern as in most Siluriform species so far, although some species-specific differences in the timing of differentiation of several digestive structures were noted, which might be related to different reproductive guilds, egg and larval size or even different larval rearing practices. According to present findings on the histological development of the digestive system in P. punctifer, some recommendations regarding the rearing practices of this species are also provided in order to improve the actual larval rearing techniques of this fast-growing Neotropical catfish species.